Motivasi Kembali dan Pemanfaatan Remitan Buruh Migran di Desa Senyiur Kecamatan Keruak - Abdul Rasyid; Suroso Suroso; Sri Agustina (Geodika: Jurnal Kajian Ilmu dan Pendidikan Geografi, 2020)
This study aims to determine: 1) the level of motivation for returning migrant workers to work abroad; 2) type and level of remittance utilization of migrant workers in the Senyiur Village, Keruak District. The method used is survey research with a descriptive approach. Data collection is done by questionnaire, interview, observation and documentation. In this study, 42 people were selected as samples with the snowball sampling technique. The subjects in this study were the people of Senyiur Village who had one or more family members to become migrant workers, and had migrated again over three times. While the data analysis technique used is percentage descriptive analysis. The results showed that: 1) the motivation of migrant workers to return work to abroad was in the high category with a percentage of 78.16%; 2) utilization of remittances for consumptive activities is in the high category with a percentage of 89.40%. While the utilization for productive economic activities is in the low category with a percentage of 10.6%.